Types of Premodifying Attributes in Lithuanian - Tekorienė, Dalija (Kalbotyra, 1989)
The study of the paratactical and hypotactical relationship between two or more premodifying adjectives, and the principles governing their sequential ordering points to the existence of three modification zones in the Lithuanian polyadjectival nominal phrases. Accordingly, three types of premodifying attributes are distinguished: specifying, characterizing (descriptive) and classifying attributes.